166 The heat is "ON" in the Neurons: neuronal stress in a sod1 Zebrafish model of MND affects neuromuscular junction integrity and causes muscle denervation. Issue 3 (9th February 2012) - Ramesh, T; McGown, A; Al Mashhadi, S; Redhead, N; Lyon, A; Bettie, C E; Shaw, P J
Abstract : Amyotrophic lateral sclerosis/motor neuron disease (ALS/MND) is a devastating disease characterised by progressive motor neuron loss leading to paralysis and death. Despite the knowledge that mutations in the SOD1 gene cause ALS relatively little is known about when and how the disease, which starts focally, spreads throughout the motor network in the CNS to cause neuronal death. Aggregation of mutant SOD1 is one proposed key mechanism contributing to neuronal injury. Cells react to the presence of misfolded proteins by inducing the heatshock response (HSR) that trigger chaperones to refold the damaged proteins, though this response is not always sufficient. Nevertheless, the HSR provides a good readout of the underlying cellular stress. We hypothesised that mutant sod1 expression in vulnerable cell groups would induce the HSR, marking cellular stress. Using the hsp70-DsRed reporter of cellular stress in the mutant sod1 transgenic fish we show that the HSR to mutant sod1 provides a sensitive tool to identify neuronal stress well before the onset of clinical symptoms. We show that the neuronal stress occurs initially in the inhibitory interneurons in the early embryonic spinal cord followed by stress in the spinal motor neurons of symptomatic adults. Most importantly, the axons of stressed motor neurons show abnormal neuromuscular junction (NMJ) with significant reduction or absence of post-synaptic contact with the muscle causing denervation. We show that riluzole, the only drug approved in the treatment of MND, significantly reduces the HSR. We can now use this zebrafish model to identify potential disease modifying therapeutic agents.